Pertumbuhan Curah Enterococcus faecalis Id 6017 dan Kemampuan Dekolorisasi Reactive Red-2 pada Medium yang Mengandung Gliserol - V. I. Meitiniarti; Morina M. Napitupulu; K. H. Timotius (Universitas Atma Jaya Yogyakarta, 2004)
Enterococcus faecalis ID 6017 can utilize glycerol as the source of carbon and energy for its growth. The present of glycerol in the medium containing Reactive Red-2 not only influenced its growth but also its ability to decolorize Reactive Red-2. The aim of this study was to investigate the growth of Enterococcus faecalis (E. faecalis) and its ability to decolorize Reactive Red-2. The microbe was grown in batch system with three different growth medium, i.e. medium which contained (i) 1.643 g/l glycerol and 0.08 g/l reactive red-2, (ii) 1.643 g/l glycerol, and (iii) 0.08 g/l Reactive Red 2. The result of this study showed that the growth of E. faecalis and its ability to decolorize Reactive Red-2 on medium contained glycerol was better than without glycerol. E. faecalis could not growth and decolorized Reactive Red-2 on medium without glycerol.